DAMPAK PENERAPAN INDONESIA - JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) TERHADAP NILAI EKSPOR IMPOR INDONESIA - Sitepu, Jesica (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2019)
This study aims to analyze the impact of the IJEPA agreement on bilateral trade (export - import) of Indonesia with Japan using 20 main commodities of trade according to the 2 digit HS code in the period 2001-2018 with the Random Effect Model (REM) estimation model. This study also analyzes whether GDP, population, and the real exchange rate of Indonesia - Japan has an influence on the development of Indonesia's export and import values. The analysis showed that both before and after the enactment of IJEPA cooperation did not have a significant effect on the value of exports from Indonesia - Japan. The variable GDP, population, and the real exchange rate have a significant effect on exports and imports. Therefore, the government of Indonesia and Japan can review the IJEPA agreement in order to increase the benefits of IJEPA.